2012
DOI: 10.3390/ijms13055307
|View full text |Cite
|
Sign up to set email alerts
|

Rational Mutagenesis of Cyclodextrin Glucanotransferase at the Calcium Binding Regions for Enhancement of Thermostability

Abstract: Studies related to the engineering of calcium binding sites of CGTase are limited. The calcium binding regions that are known for thermostability function were subjected to site-directed mutagenesis in this study. The starting gene-protein is a variant of CGTase Bacillus sp. G1, reported earlier and denoted as “parent CGTase” herein. Four CGTase variants (S182G, S182E, N132R and N28R) were constructed. The two variants with a mutation at residue 182, located adjacent to the Ca-I site and the active site cleft,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…There are now several examples of proteins that have been stabilized by the introduction of numerous mutations with cumulative small stabilizing effects (Table 1) [76,8891]. However, a clear conclusion to be drawn from others is that very large stability differences in some cases are due to only one or a few point mutations [39,45,46,9294]. Another method is to anchor the loops to the protein surface, either by non-covalent interactions or using a disulfide bridge.…”
Section: Protein Engineering To Upgrade Industrial Enzymesmentioning
confidence: 99%
“…There are now several examples of proteins that have been stabilized by the introduction of numerous mutations with cumulative small stabilizing effects (Table 1) [76,8891]. However, a clear conclusion to be drawn from others is that very large stability differences in some cases are due to only one or a few point mutations [39,45,46,9294]. Another method is to anchor the loops to the protein surface, either by non-covalent interactions or using a disulfide bridge.…”
Section: Protein Engineering To Upgrade Industrial Enzymesmentioning
confidence: 99%
“…This residue is also present in other CD8‐forming CGTases and could be responsible for the observed shift in CD product size specificity. The variant GeoT‐A1 maintained the thermostability of the parental enzyme, indicating that the A1 domain of the G825‐6 CGTase also confers thermostability properties .…”
Section: Discussionmentioning
confidence: 98%
“…Most CGTases, like other ␣-amylases, have two or more calcium binding sites [15,19,20]. Studies have suggested that the calcium binding sites in CGTases contribute to their thermostability and product specificity [15,[21][22][23]. The enzyme used in our studies, the ␤-CGTase from Bacillus circulans STB01, possesses three calcium binding sites called CaI, CaII and CaIII [15].…”
Section: Introductionmentioning
confidence: 99%